2020
DOI: 10.1371/journal.pone.0231261
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported long-term outcome after endovascular therapy of indirect dural carotid cavernous fistulas

Abstract: PurposePatient-reported long-term follow-up after endovascular treatment of indirect carotid cavernous fistulas is important, but rarely addressed in literature. We report on this issue with a special focus on the patient's view and its impact on the indication evaluation process. MethodsWe retrospectively reviewed the records of all patients (n = 33) with a minimum follow-up interval of at least 36 and up to 166 months after endovascular treatment of an indirect carotid cavernous fistula (Barrow B-D) at our i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…5,10,12,15,21 Patients with residual signs and symptoms after endovascular treatment can still show a significant improvement up to the 6-month follow-up. 9,20,22 This study shows that an improvement in visual acuity, corkscrewing of conjunctival vessels, amount of proptosis, extraocular movement limitation, presence of audible bruit, and pulsation can possibly be attributed to a successful endovascular treatment, but other factors, including supportive treatment can lead to favorable treatment outcome.…”
Section: Discussionmentioning
confidence: 78%
“…5,10,12,15,21 Patients with residual signs and symptoms after endovascular treatment can still show a significant improvement up to the 6-month follow-up. 9,20,22 This study shows that an improvement in visual acuity, corkscrewing of conjunctival vessels, amount of proptosis, extraocular movement limitation, presence of audible bruit, and pulsation can possibly be attributed to a successful endovascular treatment, but other factors, including supportive treatment can lead to favorable treatment outcome.…”
Section: Discussionmentioning
confidence: 78%
“…Subsequently 21 articles [5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (19 retrospective, 1 prospective, and 1 mixed papers) reporting patients who underwent endovascular treatment for CS-dAVFs were finally included in this review (Fig. 1).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Treatment methods consist of microneurosurgery, stereotactic radiosurgery and endovascular embolization. In recent years, fluoroscopically-guided endovascular therapy has become the gold standard treatment of CCF, as this technique allows for higher and faster cure rates as well as lower procedure-related morbidity when compared to other methods [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In particular, previous studies have shown that endovascular embolization through a transvenous route with detachable coils is considered the most effective treatment of CCF [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%